2020
DOI: 10.31234/osf.io/t3kyx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

1 What Beliefs are Associated with COVID Vaccination Intentions? Implications for Campaign Planning

Abstract: COVID vaccination intentions vary among the US population. We report the results of a nationally representative survey undertaken in July 2020 (N=889) that examined the association of six vaccine-specific beliefs with intentions to vaccinate. We find that four of the six beliefs have substantial associations with intention (Gammas between .60 and .77), that the associations mostly do not vary with gender, age, race/ethnicity, or misinformation (even though intentions do vary with each of those variables). Also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
2
4
0
Order By: Relevance
“…Our results on race support findings from earlier research that examined COVID-19 vaccine intent prior to vaccine availability 22-28 . Similarly, many published studies have found men were more willing to accept a potential COVID-19 vaccine than women 1,23,25 though one found the opposite.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results on race support findings from earlier research that examined COVID-19 vaccine intent prior to vaccine availability 22-28 . Similarly, many published studies have found men were more willing to accept a potential COVID-19 vaccine than women 1,23,25 though one found the opposite.…”
Section: Discussionsupporting
confidence: 86%
“…The effects of systemic racism, the history of research abuses among people of color in the United States, and the lived experience of mistreatment in healthcare systems likely all contribute to lower vaccination rates. 22,34,35 Increasing access to evidence-based information and implementing various forms of reflective listening with marginalized communities who are less likely to take the vaccine may decrease mistrust among healthcare workers critical to achieving a more equitable vaccine response. Additionally, while all healthcare workers in this study had been offered the vaccine in their workplaces, there may have been racial differences in actual access (e.g., ability to take time off duty to wait for the vaccine) that our study was not designed to detect.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27][28] Our results on race support findings from earlier research that examined COVID-19 vaccine intent prior to vaccine availability, including among healthcare workers. [29][30][31][32][33][34][35][36] Consistent with early reports of COVID-19 vaccination rates in the USA, we found black and Hispanic participants were less likely to receive the COVID-19 vaccine at the time of our survey. The Centers for Disease Control and Prevention reported that among persons who received the vaccine, the proportion who identified as black was lower than would be expected based on eligibility.…”
Section: Discussionsupporting
confidence: 86%
“…The potential range of messaging targets spans inoculating against specific misinformation to tapping into moral frameworks to importantly, ways to bolster trust or debunk messaging that erodes trust. Vaccine stance identified from social media importantly, should be distinguished in its value for reflecting unsolicited attitudes toward vaccines in contrast to survey research (Hornik et al, 2020). Although five profiles were discerned for each vaccine, there are substantial differences both quantitatively in the relative size of profiles, and qualitatively, how profiles distinguish users.…”
Section: Vaccine Hesitancy Profiles As Person Centered Audience Segmentation For Targeted Campaignsmentioning
confidence: 92%